Anterior Urethral Valve: A Rare But an Important Cause of Infravesical Urinary Tract Obstruction - Parmar, Jitendra P. (Pol J Radiol, 2016)
BACKGROUND: Urethral valves are infravesical congenital anomalies, with the posterior urethral valve (PUV) being the most prevalent one. Anterior urethral valve (AUV) is a rare but a well-known congenital anomaly. AUV and diverticula can cause severe obstruction, whose repercussions on the proximal urinary system can be important. Few cases have been described; both separately and in association with urethral diverticulum. The presentation of such a rare but important case led us to a report with highlighting its classic imaging features. CASE REPORT: We present a case report of AUV with lower urinary tract symptoms in a 6-year-old boy with complaints of a poor stream of urine and strain to void. Unique findings were seen on Retrograde Urethrography (RGU) and Voiding Cysto-Urethrography (VCUG), i.e. linear incomplete filling defect in the penile urethra and associated mild dilatation of the anterior urethra ending in a smooth bulge. On cysto-urethroscopy the anterior urethral valve was confirmed and fulguration was done. CONCLUSIONS: Congenital anterior urethral valve is an uncommon but important cause of infravesical lower urinary tract obstruction that is more common in male urethra. It can occur as an isolated AUV or in association with diverticulum and VATER anomalies. Early diagnosis and management of this rare condition is very important to prevent further damage, infection and vesicoureteral reflux. AUV may be associated with other congenital anomalies of the urinary system; therefore a full evaluation of the urinary system is essential.